Effect of substrate orientation on local magnetoelectric coupling in bi-layered multiferroic thin films. Issue 44 (2nd November 2018) - Naveed-Ul-Haq, M.; Webers, Samira; Trivedi, Harsh; Salamon, Soma; Wende, Heiko; Usman, Muhammad; Mumtaz, Arif; Shvartsman, Vladimir V.; Lupascu, Doru C.
Abstract : In this study we explore the prospect of strain-mediated magnetoelectric coupling in CoFe2 O4 –BaTiO3 bi-layers as a function of different interfacial boundary conditions. Abstract : In this study we explore the prospect of strain-mediated magnetoelectric coupling in CoFe2 O4 –BaTiO3 bi-layers as a function of different interfacial boundary conditions. Pulsed laser deposition fabricated thin films on Nb:SrTiO3 (100) and Nb:SrTiO3 (111) single crystal substrates were characterized in terms of their peculiarities related to the structure–property relationship. Despite the homogeneous phase formation in both films, transmission electron microscopy showed that the bi-layers on Nb:SrTiO3 (100) exhibit a higher number of crystallographic defects when compared to the films on Nb:SrTiO3 (111). This signifies an intrinsic relationship of the defects and the substrate orientation. To analyze the consequences of these defects on the overall magnetoelectric coupling of the bi-layered films, piezoresponse force microscopy was performed in situ with an applied magnetic field. The local magnetic field dependence of the piezoresponse was obtained using principal component analysis. A detailed analysis of this dependence led to a conclusion that the bi-layers on Nb:SrTiO3 (111) exhibit better strain-transfer characteristics between the magnetic and the piezoelectric layer than those which were deposited on Nb:SrTiO3 (100). These strain transfer characteristics correlate well with the interface quality and the defect concentration. This study suggests that in terms of overall magnetoelectric coupling, the Nb:SrTiO3 (111) grown bi-layers are expected to outperform their Nb:SrTiO3 (100) grown counterparts.